Social Affect and Political Disagreement on Social Media. (September 2018) - Barnidge, Matthew
The perception of political disagreement is more prevalent on social media than it is in face-to-face communication, and it may be associated with negative affect toward others. This research investigates the relationship between interpersonal evaluations (i.e., perceived similarity, liking, and closeness) and perceived political disagreement in social media versus face-to-face settings. Relying on a representative survey of adult internet users in the United States ( N = 489), the study first examines the differences between social media and face-to-face settings in terms of interpersonal evaluations and relates them to parallel differences in perceived disagreement. Results are discussed in light of important, ongoing scholarly conversations about political disagreement, tolerance toward the other side in politics, and the "affective turn" in public communication about politics.